School-Based Management In Realizing Child-Friendly Schools In The Era Of Covid-19 Pandemic In An Indonesian School - Agung, Agung Ardiansyah; Hasan Hariri; Sowiyah (International Journal of Educational Research & Social Sciences, 2021)
This study aimed to reveal and explain the implementation of school-based management (SBM) in realizing principles of child-friendly schools (CFSs) in the era of the Covid-19 Pandemic in Public Junior High School (SMPN) 1 Bandar Lampung, Lampung Province. This research used qualitative approach with a case study method. In collecting data, the researchers used the triangulation method (indepth interviews, observation, and documentstudy). This study found that implementing SBM in realizing CFS in the Covid-19 Pandemic Era was carried out by 1) school management for the purpose of contributing to achieving transparent and efficient school management and not to discouraging children’s participation in decision making, 2) active, creative, effective and fun learning, namely teaching and learning activities and positive interactions between teachers and students in schools and 3) community participation, namely direct involvement of parents and the community in improving the quality of education and increasing understanding and commitment to children’s rights.